Kainate Receptors: Role in Epilepsy - Falcón-Moya1, Rafael; Sihra, Talvinder S.; Rodríguez-Moreno, Antonio (Frontiers in Molecular Neuroscience, 2018)
Kainate (KA) is a potent neurotoxin that has been widely used experimentally to induce acute brain seizures and, after repetitive treatments, as a chronic model of temporal lobe epilepsy (TLE), with similar features to those observed in human patients with TLE. However, whether KA activates KA receptors (KARs) as an agonist to mediate the induction of acute seizures and/or the chronic phase of epilepsy, or whether epileptogenic effects of the neurotoxin are indirect and/or mediated by other type of receptors, has yet to be satisfactorily elucidated. Positing a direct involvement of KARs in acute seizures induction, as well as a direct pathophysiological role of KARs in the chronic phase of TLE, recent studies have examined the specific subunit compositions of KARs that might induce acute seizures and TLE. In the present mini-review, we discuss the use of KA as a convulsant in the experimental models of acute seizures of TLE, and consider the involvement of KARs, their subunit composition and the mode of action in KAR-mediated epilepsy. In acute models, evidence points to epileptogenesis being precipitated by an overall depression of interneuron GABAergic transmission mediated by GluK1 containing KARs. On glutamatergic principal cell in the hippocampus, GluK2-containing KARs regulate postsynaptic excitability and susceptibility to KA-mediated eplileptogenesis. In chronic models, a role GluK2-containing KARs in the hippocampal CA3 region provokes limbic seizures. Also observed in the hippocampus, is a ‘reactive plasticity’ where MF sprouting is seen with target granule cells at aberrant synapses recruiting de novo GluR2/GluR5 heteromeric KARs. Finally, in human epilepsy and animal models, astrocytic expression of GluK1, 2, 4 and 5 is reported.